Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fimmu.2022.955069
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis in inflammatory arthritis: A promising future

Abstract: Ferroptosis is a kind of regulatory cell death (RCD) caused by iron accumulation and lipid peroxidation, which is characterized by mitochondrial morphological changes and has a complex regulatory network. Ferroptosis has been gradually emphasized in the pathogenesis of inflammatory arthritis. In this review, we summarized the relevant research on ferroptosis in various inflammatory arthritis including rheumatoid arthritis (RA), osteoarthritis, gout arthritis, and ankylosing spondylitis, and focused on the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 89 publications
(147 reference statements)
0
23
0
Order By: Relevance
“…Being an important process in inflammatory diseases (Keuters et al, 2021;Chang et al, 2022), ferroptosis-based strategies have presented a long-time challenge for the clinical development of OA. In a rat OA model, treatment with interleukin (IL)-1β resulted in the decrease of collagen II and GPX4 and an increase in matrix metalloproteinases (MMPs), ROS and ion concentration, contributing to extracellular matrix (ECM) degradation and ferroptosis sensitivity (Lv et al, 2022).…”
Section: Osteoarthritismentioning
confidence: 99%
“…Being an important process in inflammatory diseases (Keuters et al, 2021;Chang et al, 2022), ferroptosis-based strategies have presented a long-time challenge for the clinical development of OA. In a rat OA model, treatment with interleukin (IL)-1β resulted in the decrease of collagen II and GPX4 and an increase in matrix metalloproteinases (MMPs), ROS and ion concentration, contributing to extracellular matrix (ECM) degradation and ferroptosis sensitivity (Lv et al, 2022).…”
Section: Osteoarthritismentioning
confidence: 99%
“…Previous studies have highlighted the correlation between iron metabolism and chronic anemia in RA patients ( Stefanova et al, 2018 ; Zhao et al, 2022b ; Chang et al, 2022 ). Recently, some studies have shown the involvement of iron metabolism in ferroptosis in RA pathogenies.…”
Section: Ferroptosis and Rheumatoid Arthritismentioning
confidence: 99%
“…This suggests that NR1D1 can potentially be used as therapeutics in the treatment of patients with RA. Various studies have indicated that ROS could be a new therapeutic target for RA treatment regarding ferroptosis ( Xie et al, 2016 ; Xie et al, 2021 ; Chang et al, 2022 ; Lai et al, 2022 ).…”
Section: Use Of Ferroptosis-related Drugs In Rheumatoid Arthritis Tre...mentioning
confidence: 99%
“…In addition, increased levels of oxidized protein products (AOPPs) and ROS in serum of AS patients have been found to induce mesenchymal stem cells (MSCs) mitochondrial dysfunction in vitro (23). These evidence of oxidative stress and mitochondrial dysfunction in AS patients inform the existence of ferroptosis in AS (18). These studies indicate that iron homeostasis is involved in the pathogenesis of AS, and the study of the correlation between the two is of potential value for the study of the mechanism and prevention of AS.…”
Section: Introductionmentioning
confidence: 95%